Proceedings of 1995 American Control Conference - ACC'95
DOI: 10.1109/acc.1995.533817
|View full text |Cite
|
Sign up to set email alerts
|

Deadlock avoidance policies for automated manufacturing cells

Abstract: This chapter considers the problem of deadlock avoidance in flexibly automated manufacturing systems, one of the most prevalent supervisory control problems that challenges the effective deployment of these environments. The problem is addressed through the modeling abstraction of the (sequential) resource allocation system (RAS), and the pursued analysis uses concepts and results from the formal modeling framework of finite state automata (FSA). A notion of optimality is defined through the notion of maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Another formalism is to describe the manufacturing system using graphs [3,5,[8][9][10][11]. In this approach the vertices represent resources and the edges represent product part flows between resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another formalism is to describe the manufacturing system using graphs [3,5,[8][9][10][11]. In this approach the vertices represent resources and the edges represent product part flows between resources.…”
Section: Introductionmentioning
confidence: 99%
“…Barkaoui and Abdallah [2], in addition to control place augmentation, used a one step look-ahead controller, which cannot avoid impending deadlocks that are more than one step away. Lawley and Reveliotis [10] identified special classes of systems that present no impending deadlocks.…”
Section: Introductionmentioning
confidence: 99%
“…A key requirement for the behavioral correctness of these systems is that they remain live, i.e., that they effectively avoid deadlocking situations where a set of executing processes is permanently blocked due to the fact that each process in this set requires for its further advancement the allocation of some resource(s) held by another process in this set. In [1], it was shown that the problem of deadlock avoidance in sequential RAS translates to the synthesis of a supervisor that will constrain the system behavior in a strongly connected component of its underlying state space, and also contains the system initial empty state. Given the current emphasis on increased resource utilization and operational flexibility, the objective is to obtain the maximally permissive liveness-enforcing supervisor (LES) that will provide the maximum behavioral latitude.…”
Section: Introductionmentioning
confidence: 99%
“…However, the implementation of the maximally permissive LES is a computationally intractable problem for most real-life applications [2]. Hence, a large body of the past results has been centered around the development of suboptimal but polynomially computable LESs that seek to assure the system liveness while maintaining considerable flexibility, through pertinent exploitation of the available information on the system structure and dynamics [1], [3]- [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation